2016
DOI: 10.1083/jcb.201603039
|View full text |Cite
|
Sign up to set email alerts
|

mito-QC illuminates mitophagy and mitochondrial architecture in vivo

Abstract: Whether mitophagy occurs within specific cellular subtypes in vivo is unclear. McWilliams et al. present “mito-QC,” a transgenic mouse containing a pH-sensitive fluorescent mitochondrial signal, allowing in vivo detection of mitophagy and mitochondrial morphology at single-cell resolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
397
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 395 publications
(440 citation statements)
references
References 44 publications
16
397
1
Order By: Relevance
“…McWilliams et al determined that mitophagy occurs at similar rates in heart and skeletal muscle using mito-QC mice. 37 They also showed that lowest levels of mitophagy occurred in the spleen while highest levels of mitophagy occurred in the liver and kidney among the tissues analyzed. Interestingly, high expression levels of mitophagy were also seen in the muscle fibers of the tongue in mito-QC mice.…”
Section: Mito-qcmentioning
confidence: 99%
See 4 more Smart Citations
“…McWilliams et al determined that mitophagy occurs at similar rates in heart and skeletal muscle using mito-QC mice. 37 They also showed that lowest levels of mitophagy occurred in the spleen while highest levels of mitophagy occurred in the liver and kidney among the tissues analyzed. Interestingly, high expression levels of mitophagy were also seen in the muscle fibers of the tongue in mito-QC mice.…”
Section: Mito-qcmentioning
confidence: 99%
“…Interestingly, high expression levels of mitophagy were also seen in the muscle fibers of the tongue in mito-QC mice. 37 An advantage of mito-QC is that mitochondria populations within different areas of a particular tissue can be monitored. For example, young mice had higher mitophagy levels in their kidney glomeruli while adult mice had lower levels of mitophagy in their glomeruli and higher levels in their cortical tubules.…”
Section: Mito-qcmentioning
confidence: 99%
See 3 more Smart Citations